THE EFFECTIVENESS OF WORDWALL EDUCATIONAL GAME MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES ON PLANT BODY PARTS - Ardiany, Dhela Teguh; Mintohari, Mintohari (Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari, 2024)
One of the learning media that is interesting and easy to find and operate in science learning is the Wordwall educational game. Therefore, this research aims to improve student learning outcomes in science and science learning through the Wordwall educational game learning media in class IV at SDN Babat Jerawat II, especially regarding plant body parts. This research is Classroom Action Research (PTK) which uses a research design from Kemmis and Taggart, consisting of two cycles with each cycle consisting of one meeting. The subjects of this research were 27 grade IV students at SDN Babat Jerawat II, consisting of 13 male students and 14 female students. Data collection techniques used include observation, structured interviews, tests (pre-test and post-test), and documentation. The research results show an increase in student learning outcomes after using the Wordwall educational game media. In cycle I, the percentage of student learning completeness reached 37% with an average score of 61.85, while in cycle II, the percentage of student learning completeness increased to 78% with an average score of 80.74. Thus, the use of the educational game media Wordwall can improve student learning outcomes in material on plant body parts in class IV SDN Babat Jerawat II.